Interfacial Shear Strength Evaluation of Pinewood Residue/High-Density Polyethylene Composites Exposed to UV Radiation and Moisture Absorption-Desorption Cycles - Soledad C. Pech-Cohuo; Irma Flores-Cerón; Alex Valadez-González; Carlos V. Cupul-Manzano; Fernando Navarro-Arzate; Ricardo Herbé Cruz-Estrada (BioResources, 2016)
In outdoor applications, the mechanical performance of wood-plastic composites (WPCs) is affected by UV radiation, facilitating moisture intake and damaging the wood-polymer interfacial region. The purpose of this study was to evaluate the effect of moisture absorption-desorption cycles (MADCs), and the exposure to UV radiation on the interfacial shear strength (IFSS) of WPCs with 40% pinewood residue and 60% high-density polyethylene. One of the WPCs incorporated 5% coupling agent (CA) with respect to wood content. The IFSS was evaluated following the Iosipescu test method. The specimens were exposed to UV radiation using an accelerated weathering test device and subsequently subjected to four MADCs. Characterization was also performed by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The absorption and desorption of moisture was slower in non-UV-irradiated WPCs, particularly in those with the CA. The UV radiation did not significantly contribute to the loss of the IFSS. Statistically, the CA had a favorable effect on the IFSS. Exposure of the samples to MADCs contributed to reduce the IFSS. The FTIR showed lignin degradation and the occurrence of hydrolysis reactions after exposure to MADCs. SEM confirmed that UV radiation did not significantly affect the IFSS.